Effect of a Short Messaging Service (SMS) intervention delivered to caregivers on energy, nutrients, and food groups intake in infant participants of the WIC program - Macchi, Alison K.; Banna, Jinan; Moreira, Stephanie; Campos, Maribel; Palacios, Cristina (Frontiers in Public Health, 2022)
Objectives: To test the effect of a weekly test message (SMS) intervention for improving feeding practices on infant intake of energy, nutrients, and specific food groups. Methods: This study was a multi-site, randomized clinical trial, in 202 caregivers of healthy term infants participating in either the Puerto Rico or Hawaii WIC program. Participants were randomized to receive weekly SMS about either infant’s general health issues (control) or SMS for improving feeding practices (intervention) to complement WIC messages for four months. Anthropometrics and demographics were assessed at baseline. A validated infant food frequency questionnaire was assessed at the four-month visit to assess intake of general food groups. Data was summarized as median (25th and 75th percentiles) or percentage and differences between study arms was compared using Mann Whitney or chi-square. Results: A total of 163 participants completed the study (n=84 control and n=79 intervention). Baseline characteristics were similar between both groups. At 4-6 months of age, compared to the control group, the intervention group had a significantly higher intake of total grains (0.28 oz; 0.00, 0.60; P = 0.033), protein (13.5g, 10.5, 18.3; P = 0.022), calcium (472 mg; 418, 667; P = 0.012), and zinc (4.39 mg; 2.61, 6.51; P = 0.028). No differences were seen in the other food groups, including breastmilk. Conclusions for practice: Feeding SMS to complement WIC messages led to higher intakes of some key nutrients but did not have an overall improvement in the intake of food groups. Messaging also did not delay the introduction of complimentary foods or improve breastfeeding rates. Future studies should evaluate the use of more intensive SMS interventions for continued care between WIC visits.